2019
DOI: 10.1016/j.celrep.2019.02.022
|View full text |Cite
|
Sign up to set email alerts
|

Trio Haploinsufficiency Causes Neurodevelopmental Disease-Associated Deficits

Abstract: SUMMARY Heterozygous coding mutations in TRIO are associated with neurodevelopmental disorders, including autism, schizophrenia, bipolar disorder, and epilepsy, and impair TRIO’s biochemical activities. To model mutant alleles, we ablated one or both Trio alleles from excitatory neurons in the cortex and hippocampus of mice. Trio haploinsufficiency increases anxiety and impairs social preference and motor coordination. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
66
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(73 citation statements)
references
References 64 publications
6
66
1
Order By: Relevance
“…In line with this, TRIO depletion in mice causes neurodevelopmental deficits associated with a decrease in brain size. 13,14 This was also supported by our experiments in Xenopus expressing different TRIO variants that resulted in phenotypes concordant with those of affected humans. This finding adds to the evidence that F0 X. tropicalis embryos produced by gene editing can be used effectively in the study of human gene variants.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…In line with this, TRIO depletion in mice causes neurodevelopmental deficits associated with a decrease in brain size. 13,14 This was also supported by our experiments in Xenopus expressing different TRIO variants that resulted in phenotypes concordant with those of affected humans. This finding adds to the evidence that F0 X. tropicalis embryos produced by gene editing can be used effectively in the study of human gene variants.…”
Section: Discussionsupporting
confidence: 69%
“…12 Heterozygous or homozygous deletion of TRIO in the hippocampus and in the cortex during early embryogenesis results in progressive defects in learning ability, sociability, and motor coordination of these mice. [13][14][15] Whole-exome sequencing studies have identified several deleterious de novo mutations in TRIO in different cohorts of individuals with neurodevelopmental disorders, including intellectual disability (ID) and/or autism spectrum disorders (ASD). [16][17][18][19] In addition, TRIO has been reported as intolerant to functional genetic variation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Trio knockout causes reduction in the extension of granule neurons from the cerebellum and severe ataxia in mice (Peng et al, 2010). Furthermore, the TRIO haploinsufficiency in mice increases anxiety; impairs sociability and motor coordination, disrupts learning capacity and spatial memory, and decreases brain and neuron size (Zong et al, 2015;Katrancha et al, 2019). In this sense, the hemizygosity of TRIO may have contributed to the clinical findings in our patient at the age of 5 months, such as the thin corpus callosum, white matter volume loss, pontine hypoplasia, and dysgenesis of the cerebellar vermis (Figures 1B,C).…”
Section: Discussionmentioning
confidence: 99%
“…It is recognized the that TRIO plays an important role in cell division, cell migration, and other functions and plays a role in synapse formation by regulating excitatory synaptic transmission (24)(25)(26). In previous mouse experiments, it was found that the lack of heterozygosity or homozygosity of TRIO in the hippocampus will lead to progressive defects in their learning and social skills (27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%